Penggunaan Reinforcement Positif Tema Lingkungan Bersih pada Motivasi Belajar IPA dan Bahasa Indonesia Kelas IV SDN 060886 Kota Medan - Raisyah Aulia Nabila Lubis; Hanna Putri Syahkira; Anggun Agia Arditha; Natasya Sihombing; Anita Yus; Yusnadi Yusnadi (Jurnal Tematik, 2025)
One of the relevant strategies to increase learning motivation is positive reinforcement, which is closely related to student motivation. Positive reinforcement is able to increase student involvement in group work through simple rewards, encouraging motivation, interest so that students are active in learning. The success of its implementation depends on the role of the teacher in designing contextual learning, such as the theme of a Clean Environment. The purpose of the research is to describe the implementation of positive reinforcement in the learning of IPA and Indonesian Language class IV SDN 060886 Medan, analyze the impact on learning motivation, and compare between subjects. This research uses a descriptive qualitative method, with a subject of 22 grade IV students. The results of this research have implications on several aspects, namely theoretical, practical, academic.